2009
DOI: 10.1073/pnas.0811313106
|View full text |Cite
|
Sign up to set email alerts
|

Single amino acid substitution in Plasmodium yoelii erythrocyte ligand determines its localization and controls parasite virulence

Abstract: The major virulence determinant of the rodent malaria parasite, Plasmodium yoelii, has remained unresolved since the discovery of the lethal line in the 1970s. Because virulence in this parasite correlates with the ability to invade different types of erythrocytes, we evaluated the potential role of the parasite erythrocyte binding ligand, PyEBL. We found 1 amino acid substitution in a domain responsible for intracellular trafficking between the lethal and nonlethal parasite lines and, furthermore, that the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
93
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 22 publications
9
93
0
Order By: Relevance
“…Moreover, sequence analysis of pyebl in fast-and slow-multiplying lines of P. y. yoelii revealed a SNP at position 2340 in pyebl that associates with the multiplication rate phenotypes. This is consistent with the findings of Otsuki and others (14) in suggesting the involvement of pyebl in determining multiplication rate phenotype in these malaria parasites. Our studies also indicated effects of at least 1 additional locus on multiplication rate, as did the findings of Otsuki and colleagues on virulence in P. y. yoelii.…”
supporting
confidence: 82%
See 4 more Smart Citations
“…Moreover, sequence analysis of pyebl in fast-and slow-multiplying lines of P. y. yoelii revealed a SNP at position 2340 in pyebl that associates with the multiplication rate phenotypes. This is consistent with the findings of Otsuki and others (14) in suggesting the involvement of pyebl in determining multiplication rate phenotype in these malaria parasites. Our studies also indicated effects of at least 1 additional locus on multiplication rate, as did the findings of Otsuki and colleagues on virulence in P. y. yoelii.…”
supporting
confidence: 82%
“…Furthermore, sequencing the pyebl gene revealed a SNP at position 2340 that distinguished all of the slow multiplying lines, which were identical at this position, from the fast multiplying line. This SNP leads to an amino acid substitution in region 6 of the PyEBL protein and is the same SNP as was identified as controlling the virulence phenotype differences between 17X and 17XYM by Otsuki and colleagues (14). Together, these results strongly imply that the SNP at position 2340 of pyebl is the major genetic determinant of both the multiplication rate and virulence difference phenotypes in the lines of P. y. yoelii that have been investigated in our two studies.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations